2017
DOI: 10.1097/sla.0000000000001840
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoffs Associated With Contralateral Prophylactic Mastectomy in Women Choosing Breast Reconstruction

Abstract: OBJECTIVE Assess postoperative morbidity and patient reported outcomes following unilateral and bilateral breast reconstruction in patients with unilateral breast cancer. BACKGROUND Relatively little is known about the morbidity associated with and changes in quality of life experienced by patients who undergo contralateral prophylactic mastectomy (CPM) and breast reconstruction. This information would be valuable for decision making in patients with unilateral breast cancer. METHODS Women undergoing maste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
81
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 28 publications
3
81
0
Order By: Relevance
“…The results revealed that patients choosing CPM with bilateral implant-based reconstruction experienced significantly improved satisfaction with breasts as measured by the BREAST-Q along with reductions in anxiety and worry about future cancer episodes on the GAD-7 and PROMIS-29 anxiety inventories. Not surprisingly, CPM was associated with greater rates of complications whether a patient received prosthetic or autologous reconstruction[26] [27]. In a separate study looking at the contribution of various factors, young age and availability of IBR, explained the greatest variation in receipt of CPM with the coefficient of determination being 32% and 29% respectively[8].…”
Section: Epidemiology and Changes In Mastectomy Patternsmentioning
confidence: 99%
“…The results revealed that patients choosing CPM with bilateral implant-based reconstruction experienced significantly improved satisfaction with breasts as measured by the BREAST-Q along with reductions in anxiety and worry about future cancer episodes on the GAD-7 and PROMIS-29 anxiety inventories. Not surprisingly, CPM was associated with greater rates of complications whether a patient received prosthetic or autologous reconstruction[26] [27]. In a separate study looking at the contribution of various factors, young age and availability of IBR, explained the greatest variation in receipt of CPM with the coefficient of determination being 32% and 29% respectively[8].…”
Section: Epidemiology and Changes In Mastectomy Patternsmentioning
confidence: 99%
“…Many patients undergo coordinated breast cancer surgery in association with an immediate reconstruction inclusive of contralateral prophylactic mastectomy (CPM). Previous studies have demonstrated increased postoperative complications in breast cancer patients who undergo bilateral mastectomy as compared with unilateral mastectomy . Patients who undergo contralateral prophylactic mastectomy have higher rates of overall complications and wound complications …”
Section: Introductionmentioning
confidence: 99%
“…2 Some studies found lower rates of regret, 2 and studies of more contemporary patients using the BREAST-Q PRO instrument 14 found that CPM with reconstruction was associated with equal or better breast satisfaction and psychosocial, physical, and sexual wellbeing. [10][11][12] …”
mentioning
confidence: 99%
“…For example, it would be helpful to include information about absolute risk 9 for surgical complications and for contralateral breast cancer after CPM, as well as more recent data on quality of life after CPM. [10][11][12] In addition, women should be provided with information about breast reconstruction options 13 and should be encouraged to consult with a reconstructive surgeon 1 to ensure that they are better informed about the potential benefits and risks of reconstructive procedures before making a final decision. Recent studies that collected patient-reported outcomes (PROs) using a wellvalidated, breast surgery-specific instrument (BREAST-Q) 14 demonstrate that breast reconstruction can improve women's satisfaction as well as their psychosocial, physical, and sexual well-being after mastectomy.…”
mentioning
confidence: 99%
See 1 more Smart Citation